Effect of Global Posture Re-Education Versus Static Stretching on Pain, Range of Motion And Quality of Life in Post-Menopausal Women with Chronic Neck Pain - Anum, Hina; Anwar, Naveed; Tauqeer, Sana; Khalid, Kehkhshan (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the effects of global posture re-education and static stretching on pain, range of motion and disability in post-menopausal women with chronic neck pain. Study Design: A quasi-experimental study. Place and Duration of Study: Sheikh Zayed hospital Rahim Yar Khan, from Jun to Dec 2020. Methodology: A total of 36 female patients between 45-65 years of age were included in the study. Patients who had received physiotherapy or manual therapy treatment for neck pain in the previous six months or had any tumour infection were excluded. There were two groups, the global posture re-education group (n=18) performed muscle chain stretching, while the static stretching group (n=18) performed conventional static muscle stretching. Visual analogue scale, neck disability index and goniometer were used for outcome measurement. Results: The results showed significant improvement in visual analogue scale score, neck disability index, flexion and extension range at four weeks and three months follow up (p<0.05). There was no significant improvement in NDI score at three months follow up (p-value >0.05). Conclusion: There was a significant difference in pain, function and disability in both groups, but the global posture reeducation group showed a maximum decrease in pain and disability and gain in ROM as compared to the static stretching group.